2015
DOI: 10.1007/s11270-015-2616-y
|View full text |Cite
|
Sign up to set email alerts
|

Microcrustaceans: biological models to evaluate a remediation process of glyphosate-based formulations

Abstract: Ecotoxicity studies using two glyphosate-based formulations (Eskoba® and Sulfosato Touchdown®) were undergone with three microcrustacean species to establish their LC50 values and to evaluate the efficacy of cleaning treatments with UV/H2O2.Samples were collected at the beginning of the process −50 mg acid equivalent per liter of glyphosate without H2O2 and at different treatment timepoints: 2, 4, and 6 h. Three microcrustacean species were used as biological models.The Eskoba® LC50 ranged between 14.49 and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Lares et al [34] observed that Faena ® was 12 times more toxic to D. exilis than to Alona guttata. Reno et al [35,36] determined the 48 h LC 50 for D. magna exposed to the four glyphosate-based formulations, Escoba ® , Roundup ® , Ultramax Panzer Gold ® , and Sulfosato Touchdown ® ; the obtained values were 29.48, 11.68, 2.12, and 1.62 mg L −1 , respectively. The differences in the acute toxicity of glyphosate (as Faena ® ) in the present work and the other commercial formulations could be attributed to the active ingredients and the type and concentration of surfactants and other adjuvants used in the different formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Lares et al [34] observed that Faena ® was 12 times more toxic to D. exilis than to Alona guttata. Reno et al [35,36] determined the 48 h LC 50 for D. magna exposed to the four glyphosate-based formulations, Escoba ® , Roundup ® , Ultramax Panzer Gold ® , and Sulfosato Touchdown ® ; the obtained values were 29.48, 11.68, 2.12, and 1.62 mg L −1 , respectively. The differences in the acute toxicity of glyphosate (as Faena ® ) in the present work and the other commercial formulations could be attributed to the active ingredients and the type and concentration of surfactants and other adjuvants used in the different formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines of the protocol proposed by the Organization for Economic Cooperation and Development OECD 202 (2004) were followed. For this, a stock culture of adult D. magna Straus 1820 females obtained from Laboratory of Ecotoxicology from the Facultad de Humanidades y Ciencias, Universidad Nacional del Litoral, Santa Fe, Argentina (Gutierrez et al, 2012; Regaldo, Reno, et al, 2014; Reno et al, 2015, 2016), was prepared in a synthetic culture medium composed of 2.4‐g MgSO 4 , 3.84‐g NaHCO 3 , 0.16‐g KCl, and 2.4‐g CaSO 4 2H 2 O in 20 L of Milli‐Q water (APHA, 1998). The pH was adjusted to 7.5 by adding 1‐M NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Ecotoxicological status of GBHs differs due to the different compositions. Thus, the LC 50 of Eskoba® and Sulfosato Touchdown® for three microcrustacean species varied in the ranges of 14.49÷95.23 mg/L and 0.31÷1.74 mg/L, respectively [6]. Addition of surfactants and other compounds (e.g., polyoxyethyleneamine, 1,4-dioxane) to commercial formulations with GBHs could considerably increase their toxicity [7,8].…”
Section: Introductionmentioning
confidence: 99%